Efisiensi Penyisihan TSS Pada Limbah Cair Laboratorium Menggunakan Karbon Aktif Ampas Tebu Teraktivasi Kimia - Farid Nauval Nugraha (Fakultas Teknik, 2026)
The water from the Water Quality Remediation and Monitoring Laboratory of the Environmental Engineering Study Program at the University of Jember has high levels of Total Suspended Solids (TSS), ranging from 2,177 to 3,282 mg/L, as well as a pH value that is not neutral, thereby exceeding applicable wastewater quality standards. This study aims to evaluate the effectiveness of activated carbon derived from sugarcane bagasse, activated using an acidic activator (0.5 M H3PO4) and a basic activator (0,6 M Na2CO3), in reducing TSS levels and improving the pH of the laboratory wastewater, as well as to analyze the effects to adsorbent bed height and activator type on adsorption performance. The activated carbon was characterized through moisture content and ash content testing, Scanning Electron Microscopy, and Fourier Transform Infrared Spectroscopy (FTIR), and the applied in a fixed-bed adsorption column with downflow configuration at varying bed heights (control, 5 cm,7 cm, and 9 cm), a flow rate of 8 mL/minute, and a contact time of 20 minutes, with two replicates. The data were analyzed using a Two-Way ANOVA. The results showed that both activated carbons met the quality requirements of SNI 06-3730-1995 and were able to effectively reduce TSS levels with removal efficiencies ranging from 96.29% to 99.54%. The best performance was achieved with activated carbon activated using Na2CO3 at a bed height of 9 cm, resulting in a final TSS concentration of 15.0 mg/L (removal efficiency of 99,54%) and final pH of 6.21–6.50,which was better that of activated carbon activated using using H3PO4 (final pH 5.42–6.23). The results of the Two-Way ANOVA test showed that type of activator had a significant effect on TSS removal (p = 0.0218) and pH increase (p = 0.0113), whereas the adsorbent bed height and the interaction between these two factors did not have a significant effect. Thus, the type of activators is the dominant factor determining the adsorption performance of activated carbon from sugarcane bagasse in a fixed-bed column system.
:: Finalisasi file repositori 4 Agustus 2026_Kurnadi
Keywords: activated carbon; adsorption; sugarcane bagasse; TSS removal